Small-molecule Inhibitors of Pseudomonas aeruginosa Biofilm Development - Chong, Matthew A. (The Meducator, 2012)
Shinerama is one of the hallmark events of McMaster’s Welcome Week. Through this student-led initiative, Mac students raised $60,000 last year for cystic fibrosis research. Interestingly, and as some undergraduates would agree, that money is being put to great use right here at McMaster’s laboratories. Here we present the exciting new discoveries of one such group: the laboratory of Dr. Lori Burrows. Matthew A. Chong is a third year student in the Bachelor of Health Sciences (Honours) Program. Funded by a generous studentship from the Canadian Cystic Fibrosis Foundation, Matthew spent his summer researching biofilm development by opportunistic pathogen Pseudomonas aeruginosa. The central focus of his project was to characterize the structure activity relationship of potent biofilm inhibitor palmitoyl-DL-carnitine.